Cover Feature: Operando Observation of Formation and Annihilation of Inhomogeneous Reaction Distribution in a Composite Electrode for Lithium‐Ion Batteries (Batteries & Supercaps 8/2019). Issue 8 (31st July 2019) - Nakamura, Takashi; Chiba, Kazuki; Fakkao, Mahunnop; Kimura, Yuta; Nitta, Kiyofumi; Terada, Yasuko; Uchimoto, Yoshiharu; Amezawa, Koji
Abstract : The Cover Feature illustrates the visualization of the formation and annihilation of inhomogeneous reaction distribution in a composite cathode for lithium‐ion batteries through operando two‐dimensional X‐ray absorption spectroscopy. This direct observation provides valuable guidelines for battery electrode design.More information can be found in theArticle by T. Nakamura et al .